THE SECOND CATALOG OF ACTIVE GALACTIC NUCLEI DETECTED BY THE FERMI LARGE AREA TELESCOPE - Ackermann, Markus; Ajello, Marco; Allafort, A.; Antolini, E.; Atwood, W. B.; Axelsson, Magnus; Baldini, Luca; Ballet, J.; Barbiellini, G.; Bastieri, Denis; Bechtol, K.; Bellazzini, R.; et al. (Astrophysical Journal, 2011)
The second catalog of active galactic nuclei (AGNs) detected by the Fermi Large Area Telescope (LAT) in two years of scientific operation is presented. The second LAT AGN catalog (2LAC) includes 1017 gamma-ray sources located at high Galactic latitudes (vertical bar b vertical bar > 10 degrees) that are detected with a test statistic (TS) greater than 25 and associated statistically with AGNs. However, some of these are affected by analysis issues and some are associated with multiple AGNs. Consequently, we define a Clean Sample which includes 886 AGNs, comprising 395 BL Lacertae objects (BL Lac objects), 310 flat-spectrum radio quasars (FSRQs), 157 candidate blazars of unknown type (i.e., with broadband blazar characteristics but with no optical spectral measurement yet), 8 misaligned AGNs, 4 narrow-line Seyfert 1 (NLS1s), 10 AGNs of other types, and 2 starburst galaxies. Where possible, the blazars have been further classified based on their spectral energy distributions (SEDs) as archival radio, optical, and X-ray data permit. While almost all FSRQs have a synchrotron-peak frequency < 10(14) Hz, about half of the BL Lac objects have a synchrotron-peak frequency > 10(15) Hz. The 2LAC represents a significant improvement relative to the first LAT AGN catalog (1LAC), with 52% more associated sources. The full characterization of the newly detected sources will require more broadband data. Various properties, such as gamma-ray fluxes and photon power-law spectral indices, redshifts, gamma-ray luminosities, variability, and archival radio luminosities and their correlations are presented and discussed for the different blazar classes. The general trends observed in 1LAC are confirmed.
CRIS-Team WoS Importer:2020-01-15